Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen